Surface sensitive K-edge absorption spectroscopy of clean and hydrogen terminated diamond (111) and (100) surfaces - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1999)
We present a detailed electron yield spectroscopy study of the pre-K-edge features of single-crystal diamond (100) and (111) surfaces which are induced by optical transitions from the C 1s core level into excited states. Both hydrogen-terminated and hydrogen-free surfaces were investigated. A sharp maximum at ℏω =287.2 eV in the spectra of the (111) and (100) surfaces is characteristic of the monohydrogenated surfaces, which is interpreted as a strongly localized intramolecular excitation within the C-H bond of a surface atom. The clean diamond surfaces show maxima in the absorption spectra at ℏω=284.6 eV for the (111) surface, and at 284.15 and 286.3 eV for the (100) surface which are interpreted as surface core excitons. From the polarization dependence of the intensities of these features and by using dipole selection rules, the point-group symmetry of the excited states involved in the optical transition is deduced. The transition energies of the absorption maxima of the clean surface are discussed in terms of pertinent band-structure calculations and excitonic effects. ©1999 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.surfac